2020
DOI: 10.1590/s1984-29612020092
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of Procamallanus (Spirocamallanus) inopinatus (Nematoda: Camallanidae) and its interactions with freshwater fish in Brazil

Abstract: This study used information about Procamallanus (Spirocamallanus) inopinatus Travassos, Artigas & Pereira, 1928 that had been published over a period of more than 90 years to investigate the infection and distribution patterns of this nematode in teleost freshwater fish in Brazil. This study was carried out using 181 samples from 82 fish species in 19 families within the five orders, with predominance of Characiformes species (71.6%). We organized a matrix-based parasite-host system in which the fish speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
4
7
0
Order By: Relevance
“…In fish from Brazil, P. (S.) inopinatus are found in the adult stage, with prevalence ranging from low to moderate, low intensity and low abundance (Neves et al, 2020), similar to that shown in the present study with H. unimaculatus. This level of parasitism can be attributed to the fact that this nematode has a complex life cycle, with transmission through prey-predator interactions (Thatcher, 2006;Neves et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fish from Brazil, P. (S.) inopinatus are found in the adult stage, with prevalence ranging from low to moderate, low intensity and low abundance (Neves et al, 2020), similar to that shown in the present study with H. unimaculatus. This level of parasitism can be attributed to the fact that this nematode has a complex life cycle, with transmission through prey-predator interactions (Thatcher, 2006;Neves et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…In H. unimaculatus from the Jari River, the parasites showed an aggregated dispersion, a typical pattern in different parasitic species in fish (Rohde et al, 1995;Guidelli et al, 2003;Tavares-Dias et al, 2013;Gonçalves et al, 2018). However, infection by P. (S.) inopinatus showed random dispersion, a pattern that is reported for nematode species of fish parasites due to its pathogenicity (Gonçalves et al, 2018;Neves et al, 2020). Gaines et al (2012) reported that P. (S.) inopinatus is pathogenic, causing severe histopathological changes in the intestine of Arapaima gigas (Schinz, 1822).…”
Section: Discussionmentioning
confidence: 90%
“…was also recorded in only one fish from one fish farm, with low parasitic indices. This species of parasite has also been reported in approximately 82 species of freshwater fish from Brazil, including A. gigas, with low values of mean intensity and abundance, in addition to prevalence ranging from low to moderate, and this low level of parasitism may be, in part, due to its complex heteroxenic life cycle (Neves et al, 2020). Similar to what is observed for Hysterothylacium sp., a strong and positive relationship of this parasite with the weight and total length of A. gigas was found.…”
Section: Parasitesupporting
confidence: 74%
“…for P. ornatus. Procamallanus (S.) inopinatus, a nematode with wide geographic distribution and is found in different species of fish in Brazil (Neves et al 2020b), was recorded here for the first time in P. ornatus. This endoparasite was the dominant species in P. ornatus and had a higher level of infection when compared to Contracaecum sp.…”
Section: Discussionmentioning
confidence: 69%